1994
DOI: 10.1002/ijc.2910570411
|View full text |Cite
|
Sign up to set email alerts
|

Association between HLA‐DQB1 alleles and risk for cervical cancer in African‐American women

Abstract: Squamous-cell carcinoma of the cervix and its precursor lesions are associated with human papillomavirus (HPV) infection. Epidemiological studies indicate that HPV infection in itself is not sufficient for cervical-cancer induction, suggesting that other factors contribute to carcinogenesis. We have investigated the potential role of host genetic background as one such factor. We screened a series of squamous-cell carcinomas of the cervix for HLA-class-II DQB1* alleles by the polymerase chain reaction and site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
55
1
4

Year Published

1996
1996
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 25 publications
(23 reference statements)
6
55
1
4
Order By: Relevance
“…4 Given the pivotal role of HLA molecules in the recognition of foreign peptides, several studies have been performed to examine the association of specific HLA alleles with HPV infection status and development of cervical cancer. In 1991, the HLA-DQw3 antigen was reported to be associated with cervical cancer in a German cohort, 4 and later studies in Spanish, 5 British 6 and African-American cohorts 7 showed similar results. Other HLA alleles have also been proposed to increase the risk of cervical cancer: DRB1*1501, 5,8 DRB1*04 and DRB1*11.…”
supporting
confidence: 67%
“…4 Given the pivotal role of HLA molecules in the recognition of foreign peptides, several studies have been performed to examine the association of specific HLA alleles with HPV infection status and development of cervical cancer. In 1991, the HLA-DQw3 antigen was reported to be associated with cervical cancer in a German cohort, 4 and later studies in Spanish, 5 British 6 and African-American cohorts 7 showed similar results. Other HLA alleles have also been proposed to increase the risk of cervical cancer: DRB1*1501, 5,8 DRB1*04 and DRB1*11.…”
supporting
confidence: 67%
“…To date, most studies have demonstrated that DQB1*03 (DQB1*0301, DQB1*0302, and DQB1*0303) is positively correlated with cervical cancer and increases its risk (Madeleine et al, 2002). This finding has been confirmed in populations in Norway (Helland et al, 1994), Japan (Nawa et al, 1995), France (Sastre-Garau et al, 1996), and an African American community (Gregoire et al, 1994). One study involving Spanish women in New Mexico also demonstrated that HPV16-positive cervical cancer patients exhibited increased DQB1*0303 expression (Apple et al, 1994).…”
Section: Introductionmentioning
confidence: 85%
“…The most consistent published evidence to date involves the HLA-DQB1*03 (DQ3) allele and HLA-DRB1*1501-DQB1*0602 haplotype. Increased risks (approximately 2-fold) for cervical cancer or malignant precursor lesions have been identified in different populations for HLA-DQB1*03 (DQ3) allele [7][8][9][10][11][12][13] or HLA-DRB1*1501-DQB1*0602 12,14-17 haplotype carriers. Other studies did not show any association with HLA-DQB1*03 [15][16][17][18][19] or HLA-DRB1*1501-DQB1*0602.…”
mentioning
confidence: 99%